2020
DOI: 10.1002/chem.202000746
|View full text |Cite
|
Sign up to set email alerts
|

Surface Design for Immobilization of an Antimicrobial Peptide Mimic for Efficient Anti‐Biofouling

Abstract: Microbial surface attachmentn egatively impacts aw ide range of devices from waterp urification membranes to biomedical implants. Mimics of antimicrobial peptides (AMPs) constituted from poly(N-substituted glycine) "peptoids" are of great interestast hey resist proteolysis andc an inhibitawide spectrum of microbes. We investigate how terminal modification of ap eptoid AMPmimic and its surface immobilization affect antimicrobial activity.W ea lso demonstrate ac onvenient surface modification strategyf or enabli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 48 publications
0
14
1
Order By: Relevance
“…However, combining the longest spacers in both branches in 4 was clearly detrimental for the activity. While the importance of having flexible linkers to support the interaction of AMP with bacteria has been documented, [42,43] in our study the incorporation of PEG chains did not bring a positive effect. It is likely that the C terminus of the molecule, which contains the sequence Lys-βAla-DOPA-DOPA (Scheme 1) acts as a pseudo-spacer, providing LF1-11 enough separation from the surface to exert its antibacterial activity.…”
contrasting
confidence: 60%
See 1 more Smart Citation
“…However, combining the longest spacers in both branches in 4 was clearly detrimental for the activity. While the importance of having flexible linkers to support the interaction of AMP with bacteria has been documented, [42,43] in our study the incorporation of PEG chains did not bring a positive effect. It is likely that the C terminus of the molecule, which contains the sequence Lys-βAla-DOPA-DOPA (Scheme 1) acts as a pseudo-spacer, providing LF1-11 enough separation from the surface to exert its antibacterial activity.…”
contrasting
confidence: 60%
“…Our results showed that the incorporation of a short PEG segment in the cell adhesive motif and none in the antimicrobial motif, combined with a cyclic RGD for cell adhesion, yielded the best biological properties, proving that the activity of the peptides may be optimized by finely tuning their conformation and orientation. However, taking into account the reported importance of having long, flexible spacers for other AMPs, [42,43] the observed effects may be contingent on the LF1-11 sequence and the method of immobilization. We foresee the reported methodology holds potential to improve the performance of diverse biomaterials.…”
mentioning
confidence: 99%
“…A powerful advantage of peptoids is the "submonomer" solid phase synthesis approach for conveniently generating sequences with diverse natural and non-natural sidechains (Zuckermann et al, 1992;Lau, 2014;Lau et al, 2017). Antimicrobial and antifouling peptoid sequences (Statz et al, 2008;Lau et al, 2012;Lohan and Singh Bisht, 2013), anti-biofouling surfaces (Hasan et al, 2020), applications in drug discovery (Zuckermann and Kodadek, 2009), diagnosing amyloid proteins (Luo et al, 2013), etc., have all been reported. Peptoid self-assembly is a rapidly emerging area, and a number of groups have reported a variety of nanostructures, including micelles (Lau et al, 2017), nanotubes (Jin et al, 2018), and nanosheets (Robertson et al, 2016;Castelletto et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, maximum protein loading, and thus maximum activity, via APTES immobilization was not reached for either single or dual coating, which corroborates with the approximate measure of a lower protein amount immobilized to the surface. Further increases in activity may be obtained by using a different linker moiety (Hasan et al 2020;Shriver-Lake et al 2017) and combining the antibacterial activity with an antifouling or antibiofilm approach (Muszanska et al 2014), which should improve the suitability of this approach for medical applications. Moreover, coatings that afford self-cleaning and (Humphrey et al 1996) was used to prepare the lysozyme structures improved durability to cotton fabrics, e.g., superhydrophobic coatings (Irfan et al 2019;Lin et al 2018;Rong et al 2019;Xu et al 2020), may be suitable for combined use with antimicrobial peptides and proteins, providing antibacterial coated cotton fabrics with long-term stability and greater activity.…”
Section: Discussionmentioning
confidence: 99%